Towards Adopting Best Practices for Disaster Management in Nigerian Higher Institutions - Michael Olarewaju Ogundele (TDMRC, Universitas Syiah Kuala, 2020)
The paper is a theoretical paper that examined the best practices being used by the Nigerian higher education administrator towards reducing the rate of disasters in the institutions. The article noted with dismay rising types of disaster in Nigerian higher institutions. However, the paper explains the concept, types of disasters, the importance of disaster management, the best practices adopted, the problems, and prospects. It was recommended that the institutions of higher learning need to adopt effective best practices to manage the available disasters in institutions to eradicate the risks of life and property destruction which constitute threats to the effective teaching-learning process and goals achievement of Nigerian higher education program.